Characterization and performance analysis for VSAT systems in Malaysia - 271213 Zahriladha Zakaria (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2004